Tsunami readiness - Rose, Simon, 1961- (Natural disasters: meeting the challenge., 2020)
Explores several devastating tsunamis from recent history, how scientists study the intensity and effects of the floods, and how geologists are using ocean sensors and data collected from satellites to understand and predict them. Includes review questions, a glossary, an index, and resources for further research.